Do registro à criação: possibilidades do uso do celular no ensino-aprendizagem em Artes da Cena - CARVALHO, Meiriluce Portela Teles (2020)
The research untitled “From the registration to creation: possibilities of the use of cellphones in the teaching-learning process in Art on Stage” is related to the Program of Post-graduation PROFARTES, Professional Master’s Program of the Federal University of Maranhão/UFMA/UDESC. The object of this research is referred to the theatrical registration and creation, in Art on Stage, through the usage of the cellphone. In this sense, the research line which this study composes is called “Theoreticalmethodological Approaches of the Teaching Practice”. The main objective is to investigate the contributions of the usage of the cellphone to the processes of registration and creation in the teaching-learning process in Art on Stage, having direct participation of the students. Therefore, the research field is the Federal Institute of Education, Science and Technology of Maranhão (IFMA) – Campus São José de Ribamar, where was developed the research with 79 students of the Technical Course, in the integrated modality, between 2018 and 2019. The scientifical problem of this study consists in verify in which ways the cellphone can contribute to the process of artistical registration and creation in the teaching-learning process in Art on Stage. Thus, understanding the relevance of the Information and Communication Technologies (ICT), the cellphone is used as a tool and registration object of the theatrical practices, of the evaluation done by the teacher and the self-evaluation realized by the students. Thereby, it is allowed to experience the act of creation, in Theatre, through the photographical performance, the video performance and the photo-movie, besides promoting more participatory, critical and reflexive classes. The methodological path adopted is related to action research, with a qualitative and quantitative approach and an exploratory-descriptive character. To the data collect, it is mentioned the documental character of the involved material, such as bibliographical approaches, semi-structured questionnaires, testimonies about experiences – through theorizing the practice of scenic exercises –, as well as writing scripts, setting scenes, games, improvisations and reading of scenic texts, as well as observing and evaluating the entire artistic process, using videos and photographs to record and create scenic practices in a critical-reflexive way. Based on that, the data is analyzed and interpreted, involving the systematization of information, through graphics and photographs. In this perspective, it is proposed to use learning strategies, in Art on Stage, based on a technological and computerized world, through which the possibilities of creation and mediation are deepened and experiences are promoted with students who contribute to the his creative and proactive development in Art/Theater classes.